2017
DOI: 10.1177/0899764017703705
|View full text |Cite
|
Sign up to set email alerts
|

Managing Dual Identities in Nonprofit Rebranding: An Exploratory Study

Abstract: Nonprofit organizations that engage in rebranding strategies face challenges reconciling normative (social or mission driven) and utilitarian (business driven) identities of their organizations. This research examines the interplay between rebranding processes and dual identities of ten rebranded charitable organizations, in particular how these identities are reflected in managers' narratives and subsequently shape rebranding strategies. The study reveals four types of rebranding strategies and the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 57 publications
0
27
0
2
Order By: Relevance
“…Generally, research has shown that the effects of managerialism depend on how an organization reacts to competing institutional norms, namely their nonprofit character and certain for‐profit tools or practices (Kravchenko & Moskvina, 2018). After all, when faced with managerialization of their processes and cultures, organizations are challenged to accommodate both their mission‐driven “normative” identity and a new, commercial “utilitarian” identity (Lee & Bourne, 2017, p. 796).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, research has shown that the effects of managerialism depend on how an organization reacts to competing institutional norms, namely their nonprofit character and certain for‐profit tools or practices (Kravchenko & Moskvina, 2018). After all, when faced with managerialization of their processes and cultures, organizations are challenged to accommodate both their mission‐driven “normative” identity and a new, commercial “utilitarian” identity (Lee & Bourne, 2017, p. 796).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The founders did not want to be identified as an NGO and hence decided to rely on contact‐based donations which led to the identity of a VO or pure nonprofit. The literature suggests stakeholders, who may not necessarily be attached with the nonprofit, hold significant power in the nonprofit (Foreman & Whetten, ; Lee & Bourne, ; Pratt & Foreman, ). This study suggests that the efforts of founders to differentiate their nonprofits from NGOs were due to the power of an external stakeholder, public's perception.…”
Section: Discussionmentioning
confidence: 99%
“…The nonprofits organizational identity is grounded in social cause and compassion (Lee & Bourne, ), with diverse organizations serving diverse social causes and facing identity tensions due to ambiguous environment (Young, , ). Considerable disagreements on defining a nonprofit organization play its due role in this confusion.…”
Section: Organizational Identity and The Non‐profit Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Employee volunteering in civic associations is also a topic of interest in the study of social movements outcomes (Walker, McCarthy, & Baumgartner, 2011). In addition, scholars find that people with utilitarian, business-driven identities are often the target of non-profit organizations as they are more likely to engage in donation behavior than people who have only an emotional attachment to the cause (Aaker & Akutsu, 2009;Lee & Bourne, 2017). Therefore, we posit that there is a positive association between having a salient occupational identity and collected donations:…”
Section: Online Social Identity As a Motivator To Collect Donationsmentioning
confidence: 97%